P746 Identification of Altered Microbial Genera at Baseline in Adalimumab Clinical Remitters and an Absence of Change in Total Microbial Composition Post Induction Treatment in the SERENE UC Study. (30th January 2023) - Morsy, Y; Pivorunas, V; Leitner, C; Birchler, T; Guay, H; Scharl, M
Abstract: Background: The gut microbiome plays an integral role in the pathogenesis of Inflammatory Bowel Disease (IBD). However, there have been a limited number of studies investigating the composition of the gut microbiome in anti-TNF-treated Ulcerative Colitis (UC) patients. The aims of this study were to 1) identify novel microbial baseline predictors of clinical response and remission to Adalimumab treatment, and 2) assess the impact of Adalimumab induction treatment on the gut microbiome of UC patients. Methods: The SERENE UC study (NCT02065622) compared the efficacy of higher adalimumab dosing regimens to the standard regimen in patients with moderately to severely active UC. 16S rRNA gene sequencing was performed on 204 stool samples from 107 UC patients at baseline and Week 8. An ANOVA test followed by Tukey HSD was used to compare microbial content within (baseline) or across (baseline vs Week 8) visits between clinical remitters (n=16), clinical responders (n=38), and patients who failed to respond to Adalimumab treatment (n=53). Clinical response was defined as a full Mayo score decrease of ≥3 points and ≥30% from baseline, plus ≥1-point decrease in rectal bleeding score or absolute bleeding score ≤1 at Week 8. Clinical remission was defined as a full Mayo score ≤2 with no sub-score >1 at Week 8. Results: There were no differences in alpha diversity in terms of richness and evenness when comparing samples from patients across response categories, or alpha and beta diversity when comparing paired samples from patients pre- and post-treatment. In addition, principal coordinate analysis of the microbiome did not highlight any clustering of the samples between response groups or visits. When stratifying patients by clinical response status at Week 8, we identified 4 genera that were significantly altered at baseline in the clinical remitters compared to the clinical responders and/or non-responders, including Dorea, Ruminococcus torques group, Subdoligranulum, and Collinsella . Unexpectedly, when comparing paired pre- and post-treatment samples within a response group, we failed to detect any significant changes on the total microbiome composition regardless of response status at Week 8. Conclusion: These findings suggest that baseline microbial composition is significantly altered in UC patients who achieve clinical remission, but that Adalimumab treatment does not significantly alter the composition of the gut microbiome after 8 weeks of treatment. Future work is focused on achieving a deeper understanding of the gut landscape in UC patients treated with Adalimumab through 1) investigation of bacterial, viral, and fungal composition by metagenomics, and 2) integration of serum metabolomics data.